Residents' Evaluation of the Effectiveness of the Urban Regeneration and Renewal Laws in the Decayed Districts of Hamidia City, Iran - Hojatollah Rahimi; Mostafa Heidari (جغرافیا و آمایش شهری منطقه‌ای, 2023)
Urban laws define power relations to change and reproduce urban spaces. The present article aimed to evaluate the effectiveness of "the law of the endorsement of revitalization, improvement and regeneration of decayed and inefficient urban neighborhoods on the process of urban regeneration in the decayed districts of Hamidia city, Yazd province, Iran, by using statistical methods including the Chi-square test, one-sample T-test and path analysis. The results showed all indicators related to urban regeneration are lower than the expected situation because regenerating drivers, including public-private participation, the socio-economic empowerment of residents, the provision of financial resources, tax incentives, building incentives, the allocation of urban infrastructure, urban land supply, the reduction of organizational bureaucracy and the improvement of inter-organizational coordination, do not work efficiently in the study area. The results of the one-sample T-test indicated that the above drivers have a significant distance from the expected conditions. According to the path analysis, the variables of socio-economic empowerment of residents, the allocation of urban infrastructure and the provision of financial resources have the most positive and overall effect on the urban regeneration of the decayed districts, respectively. Variables of the organizational bureaucracy, inter-organizational coordination and urban land supply have the most negative and overall effects, respectively. The ineffectiveness of urban regeneration law in Hamida city may result from its holistic and comprehensive approach. In urban environments like Hamida city with low diversity and low desirability of socio-economic-physical potentials, this approach can reduce the capacity of urban planners and managers to mobilize socio-economic and spatial resources to revitalize decayed districts.